Association Between Socio‐Economic Status (SES) and the Traditional Risk Factors of Cardiovascular Diseases (CVD): A Cross‐Sectional MASHAD Cohort Study Results - Fatemeh Sadabadi; Nasrin Talkhi; Mahyaar Omouri‐Kharashtomi; Mohammad Mirzaei; Sara Saffar Soflaei; Zahra Rahimi; Niloofar Shabani; MohammadReza Latifi; Mohammadreza Mohammadtaghizadeh Sarabi; Sarina Iri; Elham Moghaddas; Gordon A. Ferns; et al. (Health Science Reports)
ABSTRACT Background and Aims Socio‐economic status (SES) has been shown to be associated with cardiovascular disease. We aimed to investigate the relationship between SES and traditional risk factors for cardiovascular diseases in 35 to 65 adults of the MASHAD cohort study drawn from the second biggest city in Iran, Mashhad with a population of almost 3 million. Methods In this cross‐sectional study, subjects were divided into three categories of SES status based on their education level, employment status, and monthly income using latent class analysis (LCA). The three SES of low, medium, and high classes were compared in terms of cardiovascular disease risk factors including diabetes mellitus, metabolic syndrome, obesity, dyslipidemia, and hypertension. p value less than 0.05 was considered as significant. Results A total number of 9704 participants were included in the study. According to goodness‐of‐fit measures and entropy the three‐class model is the most optimal and suitable model here. Participants with a low SES had significantly lower means of age, physical activity level, waist circumference, systolic blood pressure and LDL‐C, and higher means of weight, and hip circumferences. Also, the prevalence of smoking, hypertension and metabolic syndrome were lower in low SES group than the two other groups. Logistic regression showed that the odds of obesity in the high SES class was 1.3‐fold higher than for the middle SES class. Moreover, the chance of metabolic syndrome and hypertension in the low SES class was respectively 0.81 and 0.83 of the middle SES class. Conclusion Lower socio‐economic was associated with metabolic syndrome and hypertension and obesity was associated with higher SES; it may therefore be necessary to develop more specific and personalized preventive policies for populations in each socio‐economic class.